Genetic ablation of retinal pigment epithelial cells reveals the adaptive response of the epithelium and impact on photoreceptors - Rebecca Longbottom; Marcus Fruttiger; R.H. Douglas; Juan Pedro Martı́nez-Barberá; John Greenwood; Stephen E. Moss (2009)
The retinal pigment epithelium (RPE) plays a critical role in the maintenance of the outer retina. RPE cell death or dysfunction drives the pathophysiology of many retinal diseases, but the physiological response of the retina to RPE cell loss is poorly understood, mainly because of the absence of suitable experimental models. Here, we generated a transgenic mouse in which an inducible Cre recombinase is expressed exclusively in the RPE under the control of the monocarboxylate transporter 3 gene promoter (RPE CreER ). This was crossed with a transgenic mouse harboring a diphtheria toxin A (DTA) chain gene rendered transcriptionally silent by a floxed stop sequence. We show that activation of DTA in the double transgenic mouse (RPE CreER /DTA) led to 60–80% RPE cell death, with surviving cells maintaining the integrity of the monolayer by increasing their size. Despite the apparent morphological normality of the enlarged RPE cells in the RPE CreER /DTA mice, functional analysis revealed significant deficits on electroretinography, and retinal histopathology showed regions of photoreceptor rosetting and degeneration although with retention of a normal vascular network. Our study reveals that whilst the RPE monolayer has a remarkable intrinsic capacity to cope with cellular attrition, specific aspects of RPE multifunctionality essential for photoreceptor survival are compromised. The RPE CreER /DTA mouse offers advantages over models that employ chemical or mechanical strategies to kill RPE cells, and should be useful for the development and evaluation of RPE-based therapies, such as stem cell transplantation.